CRITICAL PEDAGOGY: ANALYZING SOCIAL POWER AND CULTURAL IDENTITY IN MOROCCAN EFL HIGH SCHOOL GATEWAY TO ENGLISH 2 TEXTBOOK - BENDRAOU, RACHID; SAKALE, SANA; NABIL, EL OUARDI (International Journal of Language and Literary Studies, 2023)
This article aims to examine social power and cultural identity in four units of Gateway to English 2 textbook in Morocco, it is a textbook for teaching English as a foreign language for second baccalaureate. Besides, the variety of languages along with regional Moroccan dialects entail different cultural perspectives and political guidelines to project students’ orientations and national red lines to respect, since school is regarded as an area for national identities by using pedagogical implementations. In addition, the curriculum mustn’t be a vehicle to convey social inequality or bias, but rather a suitable vehicle to promote social democracy and justice for all cultural identities, and in doing so, critical pedagogy can be an effective strategy for all students to see themselves in the curriculum and reshape future guidelines for themselves and their society. The data of this study was analysed through three stages of Fairclough’s (Fairclough, 2017) approach to critical discourse analysis: description, interpretation, and explanation. The findings revealed that Gateway to English 2 textbook misrepresented Moroccan women in terms of literacy, knowledge and social position in Moroccan society and conveyed social and political guidelines. Keywords: social power and cultural identity, Gateway to English textbook, critical pedagogy